Policy and Guide for Dealing with Nuclear Disaster Threat in Indonesia - Dewi Apriliani (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
The research analyzed policies and guidelines for dealing with nuclear disaster threat in Indonesia within a collaborative approach. A case study qualitative method was used to explore and analyze the nuclear disaster threat policy and guidelines in Indonesia. The research was based on LIPI-UNESCO/ ISDR indicators on natural disaster preparedness and  IAEA parameters on nuclear emergency preparedness requirements). Results showed that  policies and guidelines on  dealing with nuclear disaster threat in Indonesia are  still deficient  (34.1%); and there is no synergy and integration of policies and guidelines on  preventing  nuclear emergency between nuclear technology users and nuclear energy regulators on one hand and disaster management policies and guidelines at the local and  national government level. Thus, enhancing  policies and guidelines on dealing with nuclear disaster threats, there is need for National Disaster Management Agency (BNPB) to undertake  collaborative governance policies with related ministries/ agencies, facilitate the integration of nuclear hazard regulations into disaster management regulations, and facilitate the establishment of national nuclear disaster management organizations.